Chemical Composition and Structural Characterization of a Basil (Ocimum basilicum L.) Leaf Extract–Bionutrient S-367B Composite - Yaya Sonjaya; Hasya Fatharani Aliya Yasyfa; Iqbal Mustapha; Billy Oktora Abdillah Fauzi (Jurnal Tadris Kimiya, 2026)
The excessive use of synthetic pesticides in horticultural production poses serious environmental and health concerns, necessitating the development of eco-friendly alternatives. This study evaluates the effectiveness of a composite biopesticide formulated from basil leaf (Ocimum basilicum L.) extract and Bionutrient S-367B on the functional response and yield of broccoli (Brassica oleracea var. italica). The extract was composited with Bionutrient S-367B at concentrations of 25%, 50%, and 75% and applied at dosages of 5, 7.5, and 10 mL/L. Phytochemical analysis confirmed the presence of alkaloids, flavonoids, saponins, and tannins, with a total phenolic content of 27.624 ± 1.468 mg GAE/g. FTIR characterization revealed key functional groups, including hydroxyl (–OH), aliphatic C–H, carbonyl (C=O), aromatic C=C, and C–N groups, indicating the presence of phenolic and non-phenolic bioactive compounds. The composite treatment showed improved functional response and yield of broccoli, particularly at a 50% concentration with a dosage of 7.5 mL/L, which produced the highest plant height, leaf dimensions, growth rate constant, and harvested biomass. However, statistical analysis indicated that these differences were not significant at the 95% confidence level (P > 0.05) across most measured parameters. These findings suggest that the integration of plant-based biopesticides with bionutrients has the potential to enhance crop performance while maintaining environmental sustainability. This study provides an integrated chemical and agronomic perspective on the application of basil leaf extract–Bionutrient S-367B composites as a promising eco-friendly strategy for sustainable broccoli production.